2015
DOI: 10.1002/nbm.3440
|View full text |Cite
|
Sign up to set email alerts
|

Proton observed phosphorus editing (POPE) for in vivo detection of phospholipid metabolites

Abstract: The purpose of this article was to compare the sensitivity of proton observed phosphorus editing (POPE) with direct (31) P MRS with Ernst angle excitation for (1) H-(31) P coupled metabolites at 7 T. POPE sequences were developed for detecting phosphocholine (PC), phosphoethanolamine (PE), glycerophosphocholine (GPC), and glycerophosphoethanolamine (GPE) on the (1) H channel, thereby using the enhanced sensitivity of the (1) H nuclei over (31) P detection. Five healthy volunteers were examined with POPE and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The use of a B1‐calibration reference marker (such as in Purvis et al) would also facilitate quantification of metabolite concentration. Further improvements in spectral SNR are possible through implementation of various imaging techniques including AMESING, DIMEPT, and proton observed phosphorus editing . Purvis et al used a 16‐channel phosphorus receive array to acquire 31 P of the liver and Valkovic et al have demonstrated the use of a 31 P birdcage for transmit in combination with a 31 P receive array for cardiac studies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a B1‐calibration reference marker (such as in Purvis et al) would also facilitate quantification of metabolite concentration. Further improvements in spectral SNR are possible through implementation of various imaging techniques including AMESING, DIMEPT, and proton observed phosphorus editing . Purvis et al used a 16‐channel phosphorus receive array to acquire 31 P of the liver and Valkovic et al have demonstrated the use of a 31 P birdcage for transmit in combination with a 31 P receive array for cardiac studies .…”
Section: Discussionmentioning
confidence: 99%
“…Further improvements in spectral SNR are possible through implementation of various imaging techniques including AMESING, 22 DIMEPT, 35 and proton observed phosphorus editing. 36 Purvis et al used a 16-channel phosphorus receive array 21 to acquire 31 P of the liver and Valkovic et al have demonstrated the use of a 31 P birdcage for transmit in combination with a 31 P receive array for cardiac studies. 37 In such an approach, both the SNR and the homogeneity of the transmit pulse can be improved.…”
Section: Contributions Strengths and Limitationsmentioning
confidence: 99%
“…Further improvements in spectral SNR are possible through implementation of various imaging techniques including AMESING, 19 DIMEPT, 27 and proton observed phosphorus editing. 28 Although not widely available, hardware improvements can also be used to boost the 31P SNR. Purvis et al use a 16-channel phosphorus receive array 18 to acquire 31P of the liver and have demonstrated the use of a 31P birdcage for transmit in combination with a 31P receive array for cardiac studies.…”
Section: Discussionmentioning
confidence: 99%
“…With the availability of higher‐field‐strength magnets for MRI in clinics and the use of efficient dedicated quadrature RF coils for the breast along with editing RF sequences, improved sensitivity of 31 P signals was seen. It is now possible to resolve individual phosphate metabolites such as the combined peak for PME and PDE and other phosphorus resonances . Moreover, the use of multi‐voxel MRS at 7 T in breast cancer patients showed detection of various phospholipid metabolites such as PCho, GPC, phosphoethanolamine, glycerophosphoethanolamine and nucleotide triphosphates, and their absolute concentrations could be determined .…”
Section: In Vivo Mrs Methods In the Study Of Breast Cancer Metabolismmentioning
confidence: 99%